2018
DOI: 10.1007/s10549-018-4755-5
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry and alternative FISH testing in breast cancer with HER2 equivocal amplification

Abstract: PurposeWhile HER2 testing is well established in directing appropriate treatment for breast cancer, a small percentage of cases show equivocal results by immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH). Alternative probes may be used in equivocal cases. We present a single community-based institution’s experience in further evaluating these cases.Patients and methodsBetween 2014 and 2016, 4255 samples were submitted for HER2 amplification testing by alternative probes, TP53, RAI1, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 39 publications
(35 reference statements)
0
30
0
3
Order By: Relevance
“…Several studies reported the use of alternative controls among patients whose cancers had ISH-equivocal status. 19 , 20 , 21 , 22 , 26 In these studies, if any HER2 -to-alternative probe ratio was 2.0 or more, the breast cancer was upgraded to ISH-positive. 19 , 20 , 21 , 26 …”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Several studies reported the use of alternative controls among patients whose cancers had ISH-equivocal status. 19 , 20 , 21 , 22 , 26 In these studies, if any HER2 -to-alternative probe ratio was 2.0 or more, the breast cancer was upgraded to ISH-positive. 19 , 20 , 21 , 26 …”
Section: Discussionmentioning
confidence: 94%
“…The second part involved reassessment of HER2 status in breast cancers from women accrued to BCIRG-005 (ClinicalTrials.gov Identifier NCT00312208 ) whose cancers had HER2 -to-CEP17 FISH ratios of less than 2.0 and an average of 4.0 to 5.99 HER2 genes per tumor cell (ISH-equivocal) or cancers with FISH ratios of less than 2.0 and average HER2 gene copies less than 4.0 per tumor cell (ISH-negative) using alternative control probes to reassess HER2 status, according to the 2013/2014 ASCO-CAP guidelines. 19 , 20 , 22 , 26 Finally, we assessed clinical outcomes in these subgroups.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…also detected RARA amplification with FISH in 71% (10 of 14 samples) of ERBB2 ‐amplified cases. RARA has been used as an alternative chromosome 17 probe in cases with equivocal HER2 FISH results (although this is no longer recommended by the updated ASCO/CAP guidelines); however, given its proximity to ERBB2 and resultant frequent coamplification, as shown in this study, it often provides little discriminatory value in such cases 21 . RARA is more notable for its role in the characteristic chromosomal translocation t(15;17)(q24;q21) in acute promyelocytic leukaemia, which leads to the fusion of RARA to the promyelocytic leukaemia gene ( PML ) 22–24 …”
Section: Discussionmentioning
confidence: 99%